Product Quality Perception and Customer Loyalty - Nwachukwu, Anthony; Benson-Eluwa, Virginia; Valentine, Ikechukwu. Ejirihugha; Keneth, Obi (Archives of Business Research, 2019)
This paper conceptualizes product quality as brand performance, reliability and innovativeness. Using the responses of 200 buyers of Detoll, the study affirms with the aid of t-test in SPSS that these dimensions of product quality affect customer loyalty significantly.